The SAGE handbook of public relations - Heath, Robert L. (Robert Lawrence), 1941-
"The SAGE Handbook of Public Relations" offers a comprehensive and detailed examination of the field. It gives academics, practitioners and students a solid review of the status of the academic literature, stressing the role that public relations can play in building relationships between organizations, markets, audiences and publics. The Handbook is divided into five parts: defining the field, seeking to explain the role public relations plays in society; examining the state of the practice by delving into the cutting-edge issues of management, ethics, gender, evaluation, public relations, education and media ; challenging academics and practitioners to identify best practices that shape their daily activities; examining the fascinating and daunting challenges the new communication technology poses for scholars and practitioners; and, a global view of the theories in international public relations as well as the trends in practice that will shape the field in the coming years. No other book in public relations is as comprehensive in its authorship and coverage of academic research, theory and best practices. Global in scope, the book's contributors constitute an academic 'who's who' of the public relations discipline. The Handbook offers a definitive source of the best insights into the definition of the field of public relations, the practice and best practices. It analyzes the impact of new communication technologies and the global challenges of international public relations.